Thinking outside the cist: interpreting a unique artefact assemblage from an Early Bronze Age burial on the Isle of Man. (December 2020) - Crellin, Rachel J.; Fowler, Chris; Gamble, Michelle
Abstract: Abstract : Recent analysis of Early Bronze Age human remains from Staarvey Farm on the Isle of Man has revealed a rare bone knife pommel and 20 other bone objects, offering insight into the importance of bone ornaments and artefact fittings at this time. This article adopts a relational typological approach to analyse the Staarvey burial and comparable assemblages, identifying patterns in the deposition of knife pommels in central and southern Britain. In exploring regional interaction in Early Bronze Age Britain and Ireland, the authors refine and move beyond traditional typologies to trace types of both objects and practice. This approach allows them to consider multiple, overlapping spheres of funerary practice and their relation to identities at different regional scales.